2017
DOI: 10.3390/nano7010021
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Potential Impacts of Metal-Based Engineered Nanoparticles in Aquatic Environments

Abstract: The specific properties of metal-based nanoparticles (NPs) have not only led to rapidly increasing applications in various industrial and commercial products, but also caused environmental concerns due to the inevitable release of NPs and their unpredictable biological/ecological impacts. This review discusses the environmental behavior of metal-based NPs with an in-depth analysis of the mechanisms and kinetics. The focus is on knowledge gaps in the interaction of NPs with aquatic organisms, which can influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(60 citation statements)
references
References 261 publications
(434 reference statements)
1
57
0
2
Order By: Relevance
“…in the digestive glands of the scallop Chlamys varia at clean sites in the Bay of Biscay, and up to 10.85 µg/g in contaminated sites, confirming that bivalves can significantly accumulate and could likely be affected by this contaminant. Few studies were conducted to evaluate the potential toxicity of CeO 2 NPs in aquatic organisms (Van Hoecke et al, 2009;Manier et al, 2011;Artells et al, 2013;Auffan et al, 2013Auffan et al, , 2014aBooth et al, 2015;Garaud et al, 2015;2016;Tella et al, 2015;Peng et al, 2017;Koehlé-Divo et al, 2018). Among them, results showed that CeO 2 NPs can act as ROS scavengers, thus protecting cells from oxidative injuries, mimicking the activity of the superoxide dismutase and catalase (Das et al, 2007;Korsvik et al, 2007;Pirmohamed et al, 2010;Ciofani et al, 2014).…”
Section: Toxic Impacts In Bivalvesmentioning
confidence: 99%
“…in the digestive glands of the scallop Chlamys varia at clean sites in the Bay of Biscay, and up to 10.85 µg/g in contaminated sites, confirming that bivalves can significantly accumulate and could likely be affected by this contaminant. Few studies were conducted to evaluate the potential toxicity of CeO 2 NPs in aquatic organisms (Van Hoecke et al, 2009;Manier et al, 2011;Artells et al, 2013;Auffan et al, 2013Auffan et al, , 2014aBooth et al, 2015;Garaud et al, 2015;2016;Tella et al, 2015;Peng et al, 2017;Koehlé-Divo et al, 2018). Among them, results showed that CeO 2 NPs can act as ROS scavengers, thus protecting cells from oxidative injuries, mimicking the activity of the superoxide dismutase and catalase (Das et al, 2007;Korsvik et al, 2007;Pirmohamed et al, 2010;Ciofani et al, 2014).…”
Section: Toxic Impacts In Bivalvesmentioning
confidence: 99%
“…Biological mechanisms inducing NPs genotoxicity are less clear. NPs are reported to have the ability to damage the genetic material by direct physical interactions as well as indirectly by the ROS generation (Li et al, 2013;Peng et al, 2017). In our study, the presence of NPs and ROS within tissues, even in low proportion, may be partly responsible for this genotoxicity leading to apoptosis.…”
Section: Discussionmentioning
confidence: 63%
“…In the environment ENPs are subject to different transformations including dissolution, agglomeration, aggregation and sedimentation, [63] which determine their stability and affect the interactions with aquatic organisms (Figure 1). The transformations of ENPs (and adsorbed metallic pollutants) strongly depend on: (i) Characteristics of ENPs (composition, size, shape, surface properties, crystal structure, etc.…”
Section: Transformations Of Mixture Of Enps and Metallic Pollutants Imentioning
confidence: 99%